Mental toughness of badminton athletes: the role of coach leadership type and coach-athlete relationship - amri hartanto; Ayu Bintan Lestari; Endang Rini Sukamti; Fauzi Fauzi; Tomoliyus Tomoliyus; Christina Fajar Sriwahyuniati; Tri Hadi Karyono (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
The coach is someone who must know about all the basic needs for the fulfilment of conditions where athletes have the opportunity to achieve achievement. The relationship between coaches of athletes who are fostered must be a relationship that reflects a common view in realising what is aspired to. This study aims to determine (1) the effect of coach leadership type on the mental toughness of badminton athletes. (2) the influence of the coach-athlete relationship on the mental toughness of badminton athletes. (3) the effect of coach leadership type and coach-athlete relationship on the mental toughness of badminton athletes. This research is quantitative with an ex post facto approach. The subjects in the study were badminton athletes in clubs in Sleman Regency Yogyakarta totalling 73 athletes (male 43, female 30). The measuring instrument with qustioner. The statistical analysis technique used the Statistical Package for Social Science (SPSS) version 21 software. The level of statistical significance was set at p-value <0.05. Based on the results of data analysis, it can be concluded that: (1) There is a significant relationship between the coach's leadership type and mental toughness in badminton athletes (t-value 4.453, p-value 0.000<0.05). (2) There is a significant relationship between coach-athlete relationship on mental toughness in badminton athletes, (t-value 2.373, p-value 0.020 <0.05). (3) There is a significant relationship between the coach's leadership type and the coach-athlete relationship on the mental toughness of badminton athletes, (F-value 40.791, p-value 0.00 <0.05) and a contribution of 52.50%. It is recommended for coaches to be able to provide enthusiasm and encouragement for athletes to continue to fight and never give up in facing every match faced in order to achieve maximum achievement and results. Develop leadership as a coach and develop interaction skills in building relationships with athletes.